FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DOSEN PADA UNIVERSITAS TRUNAJAYA BONTANG - Hellen Vera Simanjuntak (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study is a causality by using primary data and secondary data, while the object of research is the lecturer at the University Trunajaya Bontang with a total sample of 53 respondents.The aim of this study was to (1) To determine the influence of simultaneous between variable compensation, work environment, Job Promotion and Supervision of job satisfaction Lecturer at the University of Trunajaya Bontang. (2) To determine the partial variable the dominant influence on job satisfaction Lecturer at the University Trunajaya.In order to test the hypothesis analysis the authors use multiple linear regression analysis using SPSS 22. The respondents of this study is a lecturer at the University of Trunajaya, a number of 53 respondents. Results of the analysis showed that there is a positive and significant influence between variable compensation, work environment, promotion, supervision on job satisfaction, the variable dominant influence on job satisfaction is variable promotion, it is evident from the value of Standardized Coefficient Beta variable promotion is amounted to 0.428 which is greater than the other independent variable coefficients.